1997
DOI: 10.1016/s0741-5214(97)70037-5
|View full text |Cite
|
Sign up to set email alerts
|

Carotid endarterectomy in patients less than 50 years old

Abstract: Our data show that there is a high incidence of smoking and symptomatic presentation among young patients in whom carotid occlusive disease develops. CEA may be performed in young patients with low perioperative morbidity and mortality rates. Recurrent disease, late stroke, and survival rates are not significantly different than for older patients. Follow-up with serial duplex ultrasound and reoperation for symptomatic and high-grade asymptomatic restenosis may decrease the risk of late stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
6
13
1
2
Order By: Relevance
“…Our findings that smoking and a family history of atherosclerotic disease were the main risk factors for premature atherosclerosis in young adults confirmed the results of previous studies [2,3,4,5,7,8,11,16]. In a Bogalusa study [11], the autopsy results showed more distinct symptoms of subclinical atherosclerosis among younger persons with multiple risk factors aged between 2 and 39 years than among persons without risk factors.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our findings that smoking and a family history of atherosclerotic disease were the main risk factors for premature atherosclerosis in young adults confirmed the results of previous studies [2,3,4,5,7,8,11,16]. In a Bogalusa study [11], the autopsy results showed more distinct symptoms of subclinical atherosclerosis among younger persons with multiple risk factors aged between 2 and 39 years than among persons without risk factors.…”
Section: Discussionsupporting
confidence: 91%
“…In this group the higher incidence of smoking (87.5 vs. 57.4%; p < 0.001) among study patients compared with control patients is similar to that in previous studies [3,4,20,21], thereby suggesting that younger patients are more likely to be smokers at presentation. For HTN, the approximately equal prevalence in both the study group (76.1%) and the control group (71.1%) is similar to the findings of Martin et al [3] and Ballotta et al [20].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations